The Oxford handbook of international refugee law - Costello, Cathryn; Foster, Michelle; McAdam, Jane (Oxford handbooks., 2021)
"The Oxford Handbook of International Refugee Law is a comprehensive, critical work, which analyses the state of research across the refugee law regime as a whole. Drawing together leading and emerging scholars, the Handbook provides both doctrinal and theoretical analyses of international refugee law and practice. It critiques existing law from a variety of normative positions, with several chapters identifying foundational flaws that open up space for radical rethinking. The Handbook aspires to be global, both legally and geographically. Contributions assess a wide range of international legal instruments relevant to refugee protection, including from international human rights law, international humanitarian law, international migration law, the law of the sea, and international and transnational criminal law. Ultimately, the Handbook provides an account, as well as a critique, of the status quo, and in so doing it sets the agenda for future academic research in international refugee law"